New Developments in Inhibition of the Sweet Environment in a Variety of Corrosive Media: A Review - Wasan Hameed; Khalid Rashid; Anees Khadom (Engineering and Technology Journal, 2022)
This paper aims to look at how pipeline steel and crude oil storage tanks resist corrosion in aqueous carbon dioxide (CO2) environments. To this aim, we have studied different inhibitors, particularly the heterocyclic inhibitor, which is used to prevent mild steel corrosion in various situations. On mild steel, the corrosion-prevention mechanism of heterocyclic inhibitors is also investigated. CO2 corrosion is the most frequent and dreaded type of corrosion in the oil and gas industry, and corrosion inhibitors are the most effective way to fight CO2 corrosion in mild steel. Nonetheless, continual exposure to pollutants and corrosion causes such as sulfur and chromate on pipeline surfaces is unavoidable. Because of their toxicity, commercial corrosion inhibitors are being used less frequently to protect the environment. As a result of the advent of "green" chemistry and fruit waste, both of which have been demonstrated to be efficient corrosion inhibitors, plant extracts have become popular. This research aims to compile a list of carbon dioxide corrosion inhibitors that have been proved to protect against this type of attack. The material on this page is relevant to the gas and oil industries, which rely on steel pipelines and crude oil tanks to transport oil and gas products. This study will also help develop better CO2 corrosion inhibitors for the gas and oil industries.